Neither Penalised nor Prized: Feminist Legislators, Women's Representation, and Career Paths in Argentina. Issue 2 (August 2019) - Caminotti, Mariana; Piscopo, Jennifer M.
The conventional wisdom holds that party leaders punish women legislators who advocate for gender equality. We test this assumption using the Argentine case, asking two questions. First, who counts as a feminist legislator and how do we know? Second, do feminist legislators have career trajectories that indicate marginalisation or penalisation? We use bill authorship data and expert surveys to identify legislators of both sexes who champion feminist causes and who adopt a gendered, though not necessarily feminist, perspective. Comparing these categories of legislators to those in the general population, we find no meaningful differences in political careers by either legislators' gender or policy profile. In fact, many feminist champions hold prestigious positions while in congress, but this political capital results neither in punishment nor reward after congress. Women who represent women do not go on to the top posts after congress, but neither do they disappear from public life.